COVID-19: Social isolation and optimism in sport - Streeter, C. (The Sport Journal, 2020)
The purpose of this discussion is to explore communicative strategies that sport practitioners can implement during this unprecedented time of social isolation as a result of COVID-19. The goal of this discussion is to frame COVID-19 social isolation mandates as opportunities for coaches and sport practitioners to maintain mental health by revisiting their commitment to their players, to their teams, and to the industry of sport. Social isolation is a fundamental safety step that can limit the spread of COVID-19. However, research links prolonged social isolation with adverse health consequences including depression, poor sleep quality, impaired executive function, accelerated cognitive decline, and increased levels of anxiety. The social isolation that COVID-19 has thrust upon the world, including the sport industry, presents a paradox: Can social isolation manifest optimism in sport? Recommendations for coaches and sport practitioners include communicative behaviors intended to deafen the social isolation created by COVID-19. Communicative approaches discussed include empathetic language, articulation of meaning and purpose, connectedness, and strategies to overcome social isolation.